PENDAMPINGAN BELAJAR BAHASA INGGRIS BAGI REMAJA MESJID AL-MUSTAFA DI ERA GLOBALISASI - Warda, Yulia; Prihatini, Syafrina; Mardiah, Mardiah; Sari, Adinda Mutiara (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
English is a comprehensive global language used by the world community whose role is very important as a means of communication to convey ideas, feelings, and ideas in international activities to prepare for the global era. We also interpret English as a foreign language that is used for academic, professional, and work purposes. Demanding learners to master language skills namely speaking skills, reading skills, listening skills, and writing skills, this ability is known as macro skills, while micro skills in English are vocabulary, grammar, and pronunciation. For learners, the most basic thing is to master basic vocabulary (vocabulary skills) this is the main key to mastering the scope of other skills. The target of this PKM activity is the millennial generation (adolescents) who are productive age who have the opportunity and ability to learn foreign languages, namely English. As for some of the problems faced by mosque youth in recognizing and learning English as a global language including; learning English and the limitations on the knowledge of adolescents themselves. b. lack of interest and motivation in learning Islam and English. c. inappropriate delivery strategy. To answer all the above problems, what is done is to provide learning assistance that attracts teenagers' enthusiasm by using audio visuals, namely the animated video I Am the Best Muslim. The purpose of the implementation of this PKM is to provide services to the community, especially adolescents, to attract their interest in recognizing the concept of Islam in English, as well as increasing the limited knowledge of adolescents, as well as to increase interest and motivation to learn, then show that there are many ways to convey knowledge to adolescents. The implementation method in this PKM is by delivery, discussion (question and answer), and evaluation of PKM activities' success. From the results of the implementation of this service, the PKM team can conclude that youth English learning assistance with audiovisuals can attract teenagers' interest and motivation to learn in recognize the concepts of Islam and English. and can be seen from the feedback response to the discussion session and watching the English animation presented.